Exploring Icebreakers in Nursing Education Through a Mixed-Methods Design: Helpful or Harmful? - Vogelsang, Laura; Vandenberg, Shannon; Magnuson, Morgan; Walstra, Samantha (Quality Advancement in Nursing Education / Avancées en formation infirmière, 2025)
Background: Icebreakers share the common goal of promoting interaction. Despite the overwhelming positive regard for icebreakers in nursing education, they may have unintended consequences, such as highlighting inequities or perpetuating microaggressions. This research project incorporated the concept of microaggressions to explore how undergraduate nursing students experienced icebreakers within the classroom setting.Methods: This mixed-methods exploratory sequential design study used a quantitative survey followed by a semi-structured focus group using interpretive description thematic analysis.Results: A total of 43 students completed the quantitative survey, and three students participated in the follow-up focus group. The findings demonstrate that although well intentioned, icebreakers can also cause harm. Three themes were generated: revealing inequities, unveiling multiple tensions, and identifying conflict between purpose and outcome.Conclusion: Through our small study, we found that icebreakers can detract from content delivery, reveal inequities, and be divisive rather than contribute to a greater sense of belonging for students.